Risk of Bleeding Associated With Ibrutinib in Patients With B-Cell Malignancies: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Jinjin; Zhao, Ailin; Zhou, Hui; Zhu, Jinbing; Niu, Ting (Frontiers in Pharmacology, 2020)
Background: Ibrutinib is an oral covalent Bruton’s tyrosine kinase inhibitor that has been approved for chronic lymphocytic leukemia (CLL)/small lymphocytic leukemia and some other B-cell malignancies. Some studies have found an increased risk of bleeding with ibrutinib. Some studies, however, found no significant differences in the risk of major bleeding between patients treated with ibrutinib and those with other regimens. So, a systematic review and meta-analysis of randomized controlled trials (RCTs) were performed to estimate the risk of bleeding associated with ibrutinib in patients with B-cell malignancies. Methods: A systematic search of PUBMED, EMBASE, Central Register of Controlled Trials, and ClinicalTrials.gov was conducted from January 2000 to February 2020 to identify RCTs by comparing ibrutinib with other agents or placebo in B-cell malignancies. The RevMan software (version 5.3) was used to carry out this analysis, and the analyzed data were represented by risk ratios (RR) and 95% confidence intervals (CI). Results: There were 11 eligible RCTs (4,288 patients). All studies reported major bleeding, and seven studies reported overall bleeding (any-grade bleeding). Ibrutinib was associated with a significantly increased risk of bleeding (overall bleeding and major bleeding) in patients with B-cell malignancies [RR = 2.56, 95% CI 1.68–3.90, p < 0.0001 and RR = 2.08, 95% CI 1.36–3.16, p = 0.0006, respectively]. The bleeding (overall bleeding and major bleeding) risk in patients with CLL was more obvious [RR = 3.08, 95% CI 2.07–4.58, p < 0.00001 and RR = 2.46, 95% CI 1.37–4.41, p = 0.003, respectively]. There were no statistically significant differences for risk of bleeding between the subgroups based on dose and treatment setting. Conclusion: Ibrutinib was associated with a significantly higher risk of bleeding (both overall bleeding and major bleeding) in patients with B-cell malignancies, especially in CLL.